The factors influencing the adoption of bitcoin investment during covid-19 - Saleh Al-Hussaini, Abulfathi Ibrahim; Abubakar, Adamu (2021)
Bitcoin was the first virtual money to be developed in 2009 as a decentralized digital currency that can be sent by one consumer to another through the peer-to-peer bitcoin network without the use of intermediaries such as banks. Regarding finance, governments and other experts are concerned that Bitcoin can be used to circumvent currency caps, for money manipulation or illicit transactions, and could be dangerous for investors due to a lack of regulations. This paper investigates the factors influencing Bitcoin investment adoption during Covid-19. As a consequence, a methodological method was employed to accomplish these aims. The Principle of Expected Action has been introduced. Purposive sampling was used as the sampling method. A total of 101 full responses were obtained to the web-based questionnaire. Smart Partial Least Squares are used to analyse the findings (PLS). Perceived Behavior Control and Perceived Lack of Alternatives were found to have a favourable association with Intention to Invest in Bitcoin. Meanwhile, Perceived External Pressure has the reverse result, having a marginal influence on the Decision to Invest in Bitcoin. Surprisingly, Perceived Lack of Alternative completely mediates the interaction between Perceived External Pressure and Desire to Invest in Bitcoin. It is anticipated that this analysis would have a clearer picture of Investors' and Consumers' Action on Investing in Bitcoin During Covid-19.